Aural fullness and transtympanic ventilation tubes in Ménière's disease: a scoping review. Issue 6 (7th June 2019) - Sevilla, C; Goody, J; Baguley, D M; Kasbekar, A V
Abstract: Background: Ménière's disease often presents with aural fullness, for reasons that are currently not well understood. Transtympanic ventilation tube insertion has been historically used for the management of this symptom, though the nature and mechanism of effectiveness is unclear. Objective: To give an overview of the data available on the effects of ventilation tube insertion on aural fullness in Ménière's disease. Methods: The databases PubMed, Embase, Medline, Scopus, Web of Science, Central and Google Scholar were searched to identify relevant records. Records were subsequently analysed and data extracted. Results: Only two studies directly measured the effect of ventilation tube insertion on aural fullness, while three others measured it as a placebo to assess another treatment. Considerable heterogeneity was found amongst the studies, including conflicting conclusions. Conclusion: There is a paucity of evidence investigating the effect of grommet insertion on aural fullness in Ménière's disease. This work directs future research into this topic.